Evaluation of Cytologic Sample Preparations for Compatibility With Nucleic Acid Analysis. Issue 2 (20th September 2021) - Sorber, Laure; Claes, Bart; Zwaenepoel, Karen; Van Dorst, Bieke; De Winne, Koen; Fransen, Els; Wener, Reinier; Lapperre, Therese; Lardon, Filip; Pauwels, Patrick
Abstract: Objectives: In this study, the influence of several key elements of the cytologic sample workflow on DNA and RNA content was evaluated. Methods: The A549 cell line, patient-derived organoids, and pleural effusions were used to investigate the effect of (1) several collection media and delayed time to processing; (2) cytology specimens; (3) cytologic staining; and (4) formalin-fixed, paraffin-embedded (FFPE) cell block processing on nucleic acid quality and quantity as determined by fragment analyzer, Qubit analysis (Thermo Fisher Scientific), and quantitative polymerase chain reaction–based analysis on the Idylla platform (Biocartis). Results: Alcohol-based collection media (CytoRich Red [Thermo Fisher Scientific] and EtOH95%) displayed high DNA and RNA preservation capacity, while phosphate-buffered saline and, to a lesser extent, formalin were associated with high RNA quality. Cytospin and smear cytology specimens were subject to DNA and RNA loss. Cytologic staining had no further impact on sample quality, hence destaining is not necessary. Both H&E-stained and unstained FFPE sections are compatible with nucleic acid analysis, despite a strong decrease in DNA and RNA quality. Conclusions: Although several key elements of the cytologic sample workflow have an influence on DNA and RNA quality and quantity, the selection of these elements is also dependent on the downstream (ancillary) testing methods.